Metabolic syndrome prevalence in Guanajuato, Mexico’s teachers - Díaz-Cisneros, Francisco José (2010)
Objectives: To identify the prevalence of metabolic syndrome in Guanajuato, Mexico’s teachers of basic education. Design: Observational, transversal, retrospective study. Setting: Universidad de Guanajuato, Mexico. Participants: Teachers of basic education. Interventions: In 477 teachers that included 208 men and 269 women, medical evaluation and laboratory tests were done including the metabolic syndrome components (glucose, triglycerides and high density cholesterol (HDL-C) analysis), abdominal circumference measurement, blood pressure, and level of physical activity. Main outcome measures: Metabolic syndrome prevalence. Results: The prevalence of metabolic syndrome was 32.2% in men and 26.8% in women teachers. Over 40% of teachers had three risk factors for metabolic syndrome, hypertriglyceridemia the most prevalent. Concerning the level of physical activity, 24% were sedentary people, 65% hypoactive, and only 11% practiced regular vigorous exercise. Conclusions: Guanajuato’s teacher’s health profile was far from ideal, showing high prevalence of metabolic syndrome. For prevention strategies we suggest lifestyle change, especially improving diet and promoting physical activity.